Prevalence of Metabolic Syndrome in Patients with Psoriasis (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Psoriasis is a multifactorial inflammatory disease of chronicity characterized by well-defined erythematous plaques covered with silvery white scales present particularly over extensor surfaces of extrimities, trunk and scalp associated with a higher cardiovascular risk. Metabolic syndrome is one of the significant predictor of cardiovascular events.Objective: To determine the prevalence of metabolic syndrome in patients with psoriasis.Materials and Methods: This cross-sectional study was conducted in Department of Dermatology & Venereology, Combined Military Hospital (CMH), Dhaka from 01 May 2014 to 30 October 2014. One hundred four confirmed psoriasis patients were selected for this study. Complete history, thorough clinical examination including height, weight, Blood pressure (BP), waist circumference (WC) and relevant investigations were done in all patients.Results: Out of 104 patients of psoriasis, 32(30.8%) patients had metabolic syndrome and 72(69.2%) patients were without metabolic syndrome. In group I (with metabolic syndrome) majority 16(50.0%) patients belonged to age 51-60 years and in group II (without metabolic syndrome) 25(34.7%) patients belonged to age 21-30 years and the difference was significant statistically (p